Dysphoria mundi: le son du monde qui s'écroule - Preciado, Paul B. (Essai français, 2022)
«Dysphoria mundi est un texte mutant, qui hybride essai, philosophie, opéra, poésie et autofiction, afin de rendre compte de la transition planétaire en cours. Ce livre apprend au regard à distinguer ce que la propagande nihiliste mainstream cherche à dissimuler : les déplacements irréversibles qui s'opèrent dans les sphères sociales, politiques, sexuelles. Il n'est pas question d'un passé mythique ni d'un avenir messianique, mais d'un présent révolutionnaire. Le XIXe siècle était hystérique ; le XXe, schizophrène ; notre époque est dysphorique. Anxiété généralisée, troubles post-traumatiques, syndrome de dépendance, dysphorie de genre, destruction légitimée de l'écosystème... Voici l'hypothèse que propose ce livre : généraliser la notion de dysphorie afin de la comprendre non pas comme une maladie mentale, mais comme une dissidence politique. L'auteur organise une archive implacable de la fabrication/destruction nécropolitique de la subjectivité dans la modernité, et dessine une cartographie des pratiques d'émancipation susceptibles de transformer l'avenir. On dit souvent qu'il nous est devenu plus facile d'imaginer la fin du monde que de penser la fin du capitalisme. Preciado persiste à observer les preuves de pratiques alternatives à cette impasse : de nouveaux modes de vie jusqu'alors disqualifiés comme improductifs et anormaux se présentent désormais comme la seule issue.»--Page 4 de la couverture.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; disphorie; har4600; identités LGBTQIA2+; philosophie; premier cycle; périodes historiques; queer; santé; sciences humaines; sexualité; thématiques; transféminisme; études littéraires

The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Exploration of romantic relationships in adolescent females - Wisnieski, Deborah (The University of Oklahoma, 2009)
Adolescence is a time to explore and develop romantic relationships. Glamorized sexual messages and images bombard youth as they struggle to develop their sexual identity. The darker side of romance that includes teen pregnancy, STDs, and emotional pain is rarely portrayed. Because adolescent females shoulder the burden of unwanted sexual outcomes, an exploration of their experiences, both positive and negative, is the focus of this study. Current literature contains demographic information about who is at risk for unwanted pregnancies and Sexually Transmitted Diseases (STDs), but little is known from the adolescent females’ perspective, about their sexual experiences and even less about normal romantic ideation which drives sexual behavior. This qualitative study utilized ethnographic interviews to explore the experiences of 28 females ages 19-29 from four cultural backgrounds including Euro-American, African-American, American Indian, and Latina. The influence of families, peers, school, and sex education programs was explored for positive and negative experiences. Advice about romantic development to younger adolescent females was sought to gain insight into their development and how to better assist adolescent females in developing healthy romantic relationships. A multi-staged data analysis of the interviews was used to find similarities and differences among the subjects and cross culturally. Discussion of romantic behavior occurred in less than half of the nuclear families. Extended family such as aunts, uncles, and grandparents were named as significant role models by most participants and were frequently described as sources for support and occasionally available for discussion of romantic relationships. Peers were perceived to be sexually active and most behaved in a similar manner. Euro- and African-Americans placed more importance on peer groups. Reproduction was most frequently learned in the school system, rather than from family and peers. The programs were reported as woefully lacking in comprehensiveness. This study calls for policymakers to fund sex education programs for adolescents with potential participation from parents, extended family, and peers. The curriculum should address age-appropriate strategies for discussing romantic and sexual behavior. Additionally, guidelines for monitoring activities and use of new technologies that pose higher risks in early adolescence are most important. Health educators and healthcare providers can utilize these strategies when working with adolescents, families, and peers to improve their romantic relationships and decrease teen pregnancies and STDs.
Keywords: 2000 à aujourd'hui; 2000-2009; adolescentes*; amériques; discipline; mémoires/thèses; philosophie; périodes historiques; relations amoureuses; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexualité; thématiques; états-unis; étude qualitative

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales